Neuromuscular taping application to reduce work-related tension neck syndrome in “Batik” manual labor workers: a pilot controlled trial - Rahayu, Umi Budi; Putriana, D.; Setyaningrum, A.; Kusumawati, Yuli; Blow, D.; Romli, M.H. (World Scientific, 2023)
The study aimed to evaluate the effectiveness of NeuroMuscular Taping (NMT) in pain and neck disability in reducing work-related musculoskeletal stress. Methods: This study was conducted on 20 workers, with an age mean of about 53.85 years who work in the home industry of “Batik-Village” in Solo Indonesia that were divided into two groups. Intervention groups ([Formula: see text] = 10) received NMT application, while control groups ([Formula: see text] = 10) received sham treatment by the traditional approach. The collected data covered the Numerical Rating Scale (NRS) for pain and the Neck Disability Index (NDI) for a neck disability. Evaluations were made at four points of time: before, after 3 times, after 6 times of NMT application, and follow-up 15 days after the last application with mirroring duration on the control group. Results: Intervention group showed reduction on pain ([Formula: see text] = 0.000) and neck disability ([Formula: see text] = 0.000) during the intervention but only pain has prolonged effect on follow-up ([Formula: see text] = 0.001). Conclusion: NMT application to painful neck muscles in manual labor workers decreases their subjective sensation of pain during the work, after work, and after the tape removal.